‘Fake News’ about the Indonesian Past - Adrian Vickers (Journal Of Global Strategic Studies, 2022)
After the fall of the authoritarian Soeharto Regime in 1998, new versions and theories about history emerged in Indonesia. Some of these, such as theories about the origins of the nationalist movement to overthrow Dutch colonial rule, were based on sources going back to the 1950s. The case of the origins of the nationalist movement demonstrates how alternative versions of ‘truth’ can be mobilised for political ends. It also demonstrates how Islamic movements have re-centred themselves in Indonesia political and social life.